Effects of almond, dried grape and dried cranberry consumption on endurance exercise performance, recovery and psychomotor speed: protocol of a randomised controlled trial - Jonathan D Buckley; Catherine Yandell; Noah M A d'Unienville; Alison M Hill; Alison M Coates; Maximillian J Nelson (BMJ Open Sport & Exercise Medicine)
Background Foods rich in nutrients, such as nitrate, nitrite, L-arginine and polyphenols, can promote the synthesis of nitric oxide (NO), which may induce ergogenic effects on endurance exercise performance. Thus, consuming foods rich in these components, such as almonds, dried grapes and dried cranberries (AGC), may improve athletic performance. Additionally, the antioxidant properties of these foods may reduce oxidative damage induced by intense exercise, thus improving recovery and reducing fatigue from strenuous physical training. Improvements in NO synthesis may also promote cerebral blood flow, which may improve cognitive function.Methods and analysis Ninety-six trained male cyclists or triathletes will be randomised to consume ~2550 kJ of either a mixture of AGC or a comparator snack food (oat bar) for 4 weeks during an overreaching endurance training protocol comprised of a 2-week heavy training phase, followed by a 2-week taper. The primary outcome is endurance exercise performance (5 min time-trial performance) and secondary outcomes include markers of NO synthesis (plasma and urinary nitrites and nitrates), muscle damage (serum creatine kinase and lactate dehydrogenase), oxidative stress (F2-isoprostanes), endurance exercise function (exercise efficiency, submaximal oxygen consumption and substrate utilisation), markers of internal training load (subjective well-being, rating of perceived exertion, maximal rate of heart rate increase and peak heart rate) and psychomotor speed (choice reaction time).Conclusion This study will evaluate whether consuming AGC improves endurance exercise performance, recovery and psychomotor speed across an endurance training programme, and evaluate the mechanisms responsible for any improvement.Trial registration number ACTRN12618000360213.